Antioxidative response, total phenols and cadmium distribution in salicylic acid-treated euphorbia hirta L. - Delfin, Jay C.; Puzon, Juliana Janet M. (Quezon City Institute of Biology, College of Science, University of the Philippines Diliman, 2016)
The effects of exogenous salicylic acid (SA) on the antioxidative response of cadmium-exposed Euphorbia hirta L. and on the distribution of Cd within the plant were investigated Mature E. hirta plants were transferred to hydroponics, sprayed with 500 uM SA on their leaves, and exposed to 5 ppm CdCl2 for 3 days. The total chlorophyll concentrations of SA-and Cd-treated plants were significantly reduced compared with that of the control, but no significant reduction was observed in SA+Cd treated plants. Lipid peroxidation was highest in Cd-treated plants but was slightly reduced in SA-and SA+Cd-treatedplants.The levels of H2O2 significantly increased in plants treated with SA or Cd, but the increase was insignificant when SA was applied prior to Cd exposure. The results suggest that SA treatment allviated the Cd-induced oxidative damage in E. hirta by promoting the production of phytophenols and modifying the antixidant enzyme activities.
Thesis (M.S.-Biology)--University of the Philippines Diliman
Keywords: Euphorbia hirta